PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET (ROA) PADA PT. ACE HARDWARE Tbk. PERIODE 2014-2023 - Submission JORAPI; Monitia Luz Clarita; Waluyo Jati (Journal of Research and Publication Innovation, 2025)
This study aims to test the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on PT Ace Hardware Tbk for the period 2014-2023. The study uses 2 (two) independent variables, namely Current Ratio (CR) and Debt to Equity Ratio (DER) and 1 (one) dependent variable, namely Return On Asset (ROA). The research method uses the SPSS Version 25 application in addition to the tests used in this study are the Classical Assumption Test, Simple Linear Regression Analysis, Multiple Linear Regression Analysis, Determination Test, and Hypothesis Test. Based on the test results on variables with a total data of 10 years. The Multiple Linear Regression Test Equation is Y = 0.534 - 0.027X1 - 0.626X2. In the determination test, it was obtained that the effect of CR and DER on ROA was 37.2% the remaining 62.8%. Based on the results of the t-test, the calculated T for CR is 1.422 <t table 2.36462 and the Sig. value is 0.198 > 0.05, meaning that there is no influence and is not partially significant between CR and ROA. and the calculated t for DER is 1.761 <t table 2.36462 and the Sig. value is 0.122 > 0.05, meaning that there is no influence and is not partially significant between DER and ROA, in the simultaneous test, the CR and DER variables do not simultaneously affect ROA with F count greater than F table (0.196 < 4.46).